The mosses of Kangkawat research station, Imbak Canyon Conservation Area, Sabah, Malaysia - Monica Suleiman; Irmah Anwar (Universiti Malaysia Sabah, 2020)
A total of 65 species, two subspecies and one variety of mosses in 32 genera and 17 families from 102 individuals were collected during the Borneo Geographic Expedition at Kangkawat Research Station from 29th September to 3rd October 2018. This number represents ca. 10% of the taxa of mosses reported for Sabah and ca. 9% of the taxa reported for Borneo. The largest moss family recorded in this area was Calymperaceae with 18 species and one subspecies which is ca. 28% of the total taxa collected, followed by Sematophyllaceae with eight species (ca. 12%). Out of the 68 taxa of mosses from the study area, ten are new to Imbak Canyon Conservation Area including one new to Sabah, which is Chaetomitrium weberi Broth. By and large, the moss species richness of Kangkawat Research Station is typical of the conservation area.